How influencer marketing shapes the buying habits of consumers in Azerbaijan - Nabiyeva, Elnara (ADA University, 2021)
The purpose of this research is aimed at studying the influencer marketing industry in Azerbaijan, to better understand the behavior of consumers in the local market, to find out what is the perception of users of social networks of sponsored content, as well as to assess the relevance of this area in Azerbaijan. The author used both the primary and secondary data for his research. The secondary data was retrieved from academic resources for a detailed study of the available information, in order to get acquainted with the industry, to make a comparison with foreign practices, and also to emphasize the risks and positive aspects of the influencer marketing. In order to address the research question, the researcher chose a mixed methods approach, meaning that the data was obtained through several approaches, such as survey with a Likert Scale Data measuring people’s attitude, two sets of influencers which were considered to be macro and micro opinion leaders, as well as semi structured – interviews, which were online based, due to the circumstances, with marketing professionals. To address the question from different perspectives and to be able to make comparisons, the researcher selected mixed methods approach which gave the opportunity to use the advantages of both qualitative and quantitative research techniques. Since the research includes a human factor, namely human behavior and factors that influence a user's decision making, the inductive approach was chosen to be the most appropriate way to code the data from interview. Using the primary data and facts from the secondary data, the researcher was able to assess the research question, bring the work to its logical conclusion, and provide some recommendations.
Keywords: Influencer -- Azerbaijan.; Marketing industry.; Influencer marketing.; Business